Black South African English in relation to other second-language Englishes of Africa - Morreira, Kirsten Lee (Department of English Language and Literature, 2023)
The existence of distinctive varieties of second language English in Africa has, by now, been long recognized. Such L2 Englishes are known to arise in situations where the socioeconomic value of English is high, but where restricted access to native speaker varieties of the language results in the establishment and, eventually, the generational transmission of a new secon4:1anguage variety. These 'New Englishes' have been found to possess certain structural similarities across geographical boundaries, while still retaining distinctively local features. The New Englishes of Africa, in particular, have been observed by several authors to be sufficiently similar to warrant the possible use of 'African English' as a generalized cover term for the group. Nevertheless, the continued study of L2 English varieties in separate geographical and political areas within Africa is an indication of the existence of distinctive, if in many ways similar, local varieties. The object of this dissertation is a systematic comparison of the syntactic structure of varieties of sub-Saharan L2 English, taking as a basis Black South African English as a point of comparison. The syntactic structures of these varieties are examined in order to determine the nature and extent of the structural similarities between them, as well as the degrees of difference that occur. It is widely acknowledged that of those sets of features of the New Englishes which differ from Standard English, syntactic variation forms the smallest part. Nevertheless, such variation does exist, both in differences between the New Englishes and the standard(s), and between the New Englishes themselves. The syntactic features of Black South African English are discussed and compared with those of other African Englishes, in order to develop a means of describing such language varieties in relation to one another, and of assessing the extent to which certain of their syntactic features can be recognized as pan-African. A more detailed analysis of the structure of the relative clause in the varieties is given, drawing on theories regarding the origin of certain New English features, as a means of explaining the non-standard occurrence of resumptive pronouns within the relative clause. Finally, the need for corpus-based research into African Englishes is stressed, as a means of determining the frequency of occurrence of those features identified as typical of the varieties.